Barriers to listing for HIV‐infected patients being evaluated for kidney transplantation. Issue 6 (5th October 2017) - Lee, Dong Heun; Boyle, Suzanne M.; Malat, Gregory E.; Kern, Christopher; Milrod, Charles; DeBellis, Shannon; Harhay, Meera N.; Ranganna, Karthik; Guy, Stephen; Talluri, Sindhura; Bias, Tiffany; Doyle, Alden
Abstract: Human immunodeficiency virus (HIV)‐infected patients have excellent outcomes following kidney transplantation (KT) but still might face barriers in the evaluation and listing process. The aim of this study was to characterize the patient population, referral patterns, and outcomes of HIV‐infected patients who present for KT evaluation. We performed a single‐center retrospective cohort study of HIV‐infected patients who were evaluated for KT. The primary outcome was time to determination of eligibility for KT. Between 2011 and 2015, 105 HIV‐infected patients were evaluated for KT. Of the 105 patients, 73 were listed for transplantation by the end of the study period. For those who were deemed ineligible, the most common reasons cited were active substance abuse (n = 7, 22%) and failure to complete the full transplant evaluation (n = 7, 22%). Our cohort demonstrated a higher proportion of HIV‐infected patients eligible for KT than in previous studies, likely secondary to advances in HIV management. Among those who were denied access to transplantation, we identified that many were unable to complete the evaluation process, and that active substance abuse was common. Future prospective studies should examine reasons and potential interventions for the lack of follow‐through and drug use we observed in this population.